Connotative meanings in political headlines of a local newspaper - Chutya Noerfida; Zulfadli Abdul Aziz; Kismullah Abdul Muthalib (TALENTA, 2026)
This descriptive qualitative research aims to identify the types of connotative meanings found in political news headlines of Serambi News, an online local newspaper published in Aceh Province. In analyzing this study, the writer used Leech’s theory of meaning. The data were drawn from 65 political news headlines, selected for the presence of words or phrases with connotative meanings. The data were analyzed by examining the expressions in the headlines and reading the full articles to understand the context. The analysis revealed 44 connotative meanings categorized into three types: negative, neutral, and positive. The results showed that negative connotations were the most dominant type, representing 45.45% of the total findings, followed by neutral (29.55%) and positive (25%). This indicates that political headlines in Serambi News tend to adopt a provocative, critical tone to attract readers’ attention. Moreover, the study highlights that the interpretation of connotative meanings can vary across contexts, cultures, and individual perceptions. Therefore, understanding connotative meaning is essential for both media producers and consumers in shaping and interpreting political discourse.